Rheological study of reinforcement of agarose hydrogels by cellulose nanowhiskers. (13th February 2015) - Le Goff, Kevin J.; Gaillard, Cedric; Helbert, William; Garnier, Catherine; Aubry, Thierry
Highlights: The structure and rheology of agarose hydrogels filled with cellulose nanowhiskers were studied. A significant strengthening effect due to addition of nanowhiskers at low concentrations was observed. Results suggest that the reinforcement effect is due to nanowhiskers induced slight changes in agarose network structure. Abstract: The influence of the addition of tunicate cellulose nanowhiskers on the structural and rheological properties of an agarose hydrogel matrix has been studied, with the objective to design innovative green material, with good mechanical properties. The cellulose nanowhiskers were characterized using transmission electron microscopy, and their charge surface density was determined by a titration method. Oscillatory shear and stress relaxation tests were performed in order to characterize the rheological properties of the agarose matrix, and of the agarose hydrogels filled by nanowhiskers at volume fractions below 0.2%. The results show a significant reinforcement effect due to the addition of nanowhiskers, and suggest changes in the matrix network structure induced by the cellulose nanoparticles.